Work simply : embracing the power of your personal productivity style - Tate, Carson (Portfolio Hardcover, 2015)
"Many of us try the popular productivity solutions and tools, only to find ourselves falling further behind and more frustrated than ever. We end up spending more time managing our calendars and to-do lists than doing actual work. Carson Tate says that's because our brains often don't work the way the experts assume. She has helped thousands of men and women become better at time management and productivity, by using a unique assessment tool that helps people discover their individual productivity styles. In Work Simply, she explains the four major styles--Prioritizer, Planner, Arranger, and Visualizer-- and offers invaluable tactics for leveraging your personal style instead of fighting it. She makes it much easier to manage your attention, get more done, tame your inbox, set and reach goals, and much more"--